Experimental study on bolted and anchored beam-to-column joints of prefabricated concrete frames. Issue 2 (January 2020) - Zhang, Xizhi; Hao, Jiashu; Duan, Dongchao; Xu, Shengbo; Zhang, Shaohua; Yu, Houxin
A new type of beam-to-column joint used in prefabricated concrete frames was proposed in this study. In this joint, the longitudinal bars at the top of the beam are anchored to the column using straight thread sleeves, and the bars at the bottom are welded to the steel fastener that is bolted to the column. Cyclic loading tests of three specimens, namely, two beam–column joints of this type and a cast-in-place beam–column joint, were conducted to study the seismic behavior and feasibility of this type of joint. The difference between the two prefabricated joints is the shape of the holes on the end plate. Failure modes of the specimens were observed and analyzed. The hysteretic curves, bearing capacities, stiffness degeneration, ductility, and energy-dissipating capacities of the specimens were compared and studied. Test results indicated that all beam–column joints exhibited beam hinge failure. No slippage was observed between the concrete and horizontal plates of the steel fasteners used in the new type of joint. The bearing capacity and initial stiffness of both prefabricated specimens compared with the cast-in-place ones were increased. The steel fastener could increase the distance between the plastic hinge and the side surface of the column while enlarging the length of the plastic hinge. The trend of energy dissipation and stiffness degeneration of the specimens were similar, and the ductility coefficient ranged from 2.7 to 4.91. The displacement angles of the joints exceeded 1/50 before the failure of the specimens. The mechanical behavior of both prefabricated joints was similar, but the joint with U-shaped holes on the end plate was convenient to create.